Enhancement of antimicrobial efficacy of neem oil vapour treated cotton fabric by plasma pretreatment. (November 2015) - Anitha, S.; Vaideki, K.; Jayakumar, S.; Rajendran, R.
Abstract : This paper deals with the study on the reaction between DC air plasma treated cotton cellulose and bioactive compounds present in the neem oil vapour. Untreated cotton fabric (control) and DC air plasma pretreated cotton fabric were exposed to neem oil vapour to impart antimicrobial activity, and the process parameters such as temperature and treatment time were optimised to obtain the maximum antimicrobial activity. Gas chromatography–mass spectrometry analysis was carried out to identify the bioactive compounds present in neem oil vapour. The effect of plasma treatment in modifying the fabric surface was explored by analysing the changes in the cellulose structure, crystallinity and morphology of fabric surface using attenuated total reflection–Fourier transform infrared spectroscopy (ATR-FTIR) spectra, X-ray diffractogram and scanning electron microscopy (SEM) micrographs. The reaction between cellulose and bioactive compound present in neem oil vapour was analysed using the ATR-FTIR spectra. The change in morphology after treatment with neem oil vapour was analysed using SEM micrographs.